Efek Samping Lama Aplikasi dari Bleaching Agent Hidrogen Peroksida 40% Terhadap Kekasaran Permukaan Resin Komposit Tipe Nanofill - Yulviansyah, Izfan; Widjijono, Widjijono; Irnawati, Dyah (Jurnal Material Kedokteran Gigi, 2013)
Bleaching is a dental treatment chemically on the vital and non vital teeth undergoing discoloration. One technique is in office bleaching . Application of bleaching agent is not only touching the healthy tooth tissue, but also potentially touched restorative nanofill dental composite resins. Materials research is resin composite nanofil (Filtek Z350, 3 m, USA) and the bleaching agent 40% hydrogen peroxide (Opalescense Boost, USA). Disc-shaped sample (diameter 10 mm, thickness 2 mm) as many as 12 samples and divided into 3 groups each sample 4. The samples applied with bleaching agent 40% hydrogen peroxide at room temperatures (25 C) and contact time: 30 minutes, 45 minutes, and 60 minutes. Surface roughness was measured before and after application of bleaching. Surface roughness was measured before and after application of bleaching. Statistical analysis using a one way ANOVA and LSD 0,05. The results showed the average delta composite resin nanofil roughness with time sequential contacts 30, 45 and 60 minutes is 0,040 0,016 µm ± 0,045 µm ± 0.025, and 0.025  ± 0.125 µm. ANOVA test showed that there is a sinificant influence of variation of long application of hydrogen peroxide 40% against a nanofill composite resin surface roughness (p< 0.05). Test LSD indicates there is a significant difference between the delta’s average surface roughness on all groups, except the group of 30 and 45 minutes. Conclusion this research is a variation time contacts of 40% hydrogen peroxide application increases the surface roughness of a composite resin nanofil.